Economic crisis and international migration: The case of Spain - Carmen Ródenas; Monica Martì; Mirostava Kostova (European Regional Science Association (ERSA), 2013)
Spain has become a country of immigration very fast and in an unusual way. At the beginning of the year 2000, foreigners represented barely 2% of the total population, a figure which rose to 12% and exceeded 5.7 million in 2012. Considering its population size, Spain was the country which received the highest annual average net inflow of about 528,000 migrants (2000-2007). Other neighboring countries, such as Germany had an annual average net inflow of 107,000, the UK and France with 217,000 and 125,000, respectively, and even Italy left far away with its annual net inflow of 286,000. This remarkable increase in the foreign population took place mainly between 2000 and 2007, years which were characterized by a strong economic expansion. In the Spanish case, there was a very strong relationship between these waves of immigrants - 80% of whom were of working age and most of them came from low income countries-, and the GDP and employment growth in Spain. In 2012, the change in the economic cycle since 2007 has established a new situation with regard to mobility. The severity of the Spanish crisis and the rise in unemployment among immigrants would suggest that a massive emigration or return to emigrantâ??s countries of origin is taking place. However, if we follow the demographic, social and economic migrant footsteps in this country, this hypothesis has not so far been confirmed. In fact, when we analyze the legal foreign residents' data over time, information on the enrollment of non-nationals in primary and secondary education, new citizenships and recent remittances sent abroad statistics, we find little evidence of a mass exodus. Neither do we find sufficient evidence when we analyze migration flows by large geographical areas. These facts raise some interesting questions. The specific characteristics of the Spanish case are enough to convince that this country is an interesting case study, even more so because we have the possibility of studying the behavior of all foreign migrants (both regular and irregular are set out in our statistical sources) in a context of recession and in an economy, like the Spanish one, which has large shadow sector. Thus, the paper analyzes the impact of the economic crisis on migration in Spain. It is a preliminary descriptive draft in which the basic lines of the main changes regarding international immigrants are drawn. KEYWORDS: international migration, economic crisis, shadow economy. JEL Codes: J61, F22, R23
Keywords: J61; F22; R23; 330; international migration; economic crisis; shadow economy